PERAN ORANG TUA DAN PONDOK PENDIDIKAN ISLAM DALAM MENINGKATKAN MOTIVASI SISWA - Faiqotul Masruro; Ahmad Zubaidi (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2026)
This study explores the collaboration between parents and pesantren administrators in enhancing students’ learning motivation at Pondok Pesantren Zainul Anwar, Probolinggo. The research aims to examine the forms, strategies, and impacts of collaborative efforts between parents and pesantren leaders in supporting students’ educational development. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. The findings reveal that the collaboration is manifested through periodic meetings, digital communication via WhatsApp groups, parental participation in religious and educational activities, and consistent moral and material support. This synergy creates a harmonious relationship between home and pesantren environments, significantly strengthening students’ learning enthusiasm, discipline, and responsibility. The study highlights that the collaboration model aligns with Bronfenbrenner’s Ecological Systems Theory and Epstein’s School-Family-Community Partnership Model, emphasizing that active family engagement promotes academic and socio-emotional development. Furthermore, Bandura’s Social Learning Theory supports the idea that exemplary behavior and emotional reinforcement from parents and educators enhance intrinsic learning motivation. This research concludes that strong collaboration between parents and pesantren administrators fosters holistic student development. It recommends further institutional support through integrated communication systems and religious parenting programs to sustain motivation and improve educational outcomes in Islamic boarding schools.